Financial Technology on Halal MSMEs in Indonesia: Literature Study - Ardiansyah, Muhammad Rajab (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
Halal Micro, Small, and Medium Enterprises are businesses sector with great potential for economic growth, so halal MSMEs can be a driver of Indonesia's target in terms of becoming a halal center in the world. The development of halal MSMEs must be adapted to the times, where the use of Financial Technology should currently be a weapon for halal MSME actors in facilitating consumers in transactions and as financial records. However, according to the data from the Ministry of Cooperatives and SMEs that there are still many MSME actors including Halal MSMEs who have not yet touched on technology in their financial management, this can be seen from the percentage figure which has only reached 13% of MSMEs adopting digital technology. This research design using a qualitative research approach by conducting a literature study 8 papers on Google Scholar that are relevant to the research question. The results of this study suggest that the impact of Fintech is huge in helping MSME actors. Fintech has made very significant changes and successes. All services that use e-commerce are faster, easier, and guaranteed security, and all levels of society who use digital economic technology can enjoy them thoroughly.